Design of annular linear induction pumps for space nuclear reactors - Carlos O. Maidana (2018)
© 2014, The Author(s). In space reactors as well as in other types of semi-transportable small modular reactors, weight, reliability and efficiency are of fundamental importance. Furthermore, for space reactors liquid metals as working fluids are the only option due to the working environment characteristics that outer space provides. For space power systems, the induction electromagnetic pump is inherently more reliable than the conduction electromagnetic pump. The annular linear induction pump also has several advantages over its flat counterpart because it has greater structural integrity, it is more adaptable to normal piping systems, and it allows greater design freedom in the coil configuration. The annular design also has a basically greater output capability since the path followed by the induced currents has a lower resistance than the path followed in a corresponding flat pump. The design work of ALIP-type thermo-magnetic systems using the electric circuits approach is described as well as the fundamental ideas behind the development of modelling and simulation techniques for the development of an optimized design methodology using “first principles”. This project, involves the use of theoretical, computational and experimental tools for multi-physics analysis as well as advanced engineering design methods and techniques.